The Journey of Two Decades of Special Autonomy in Resolving Security Issues in Papua - Khalimatus Sa'diyah (Social Science Studies, 2022)
The problems in Papua have not yet been entirely resolved. Various issues ranging from poverty, minimal access to education, violations of human rights, and poor health facilities are part of the concept of human security introduced by the UNDP Report 1994. However, the problems above have not been accommodated properly in Papua. The essence of the presence of special autonomy is aimed at resolving human security in Papua. The purpose of this article is to look at the special autonomy arrangements in responding to security issues. This issue is interesting to study considering that so far it is unrelated to each other. But actually, the concept of human security and special autonomy are two linear things. If we want to improve welfare in Papua, the issue of security is a requirement that must be met. This research uses a qualitative approach with a literature study method. The author collect data through sources relevant to the topic of writing such as journals, books, and other literature. The results of study indicate that the implementation of special autonomy in Papua has not been able to reach security issues. This has resulted in a welfare approach in Papua characterized by a traditional security approach. Therefore, the welfare of Papua continues to budge and the welfare narrative still triggers ongoing conflicts. Various central problems ranging from economic inequality, low quality of education, poor health facilities and infrastructure, human rights violations, and so on are still happening.